Mathematical Modeling of Bread Baking: A Bibliometric Review of PDE-Based Multiphysics Approaches - Afriansyah, Dilla; Gita Dwikasari, Lingga (Griya Journal of Mathematics Education and Application, 2025)
This study examines how partial differential equations serve as the mathematical foundation for modeling the coupled heat and mass transfer processes occurring during bread baking. Through a systematic bibliometric approach, data from major scientific databases were analyzed using mapping techniques to identify dominant themes, research clusters, and developmental trends in mathematical modeling for bread baking. The findings indicate that heat transfer, moisture migration, crust formation, and dough thermomechanics constitute the core of this field, with diffusion and convection–diffusion equations forming the principal modeling framework. Network, overlay, and density visualizations reveal a growing adoption of advanced numerical schemes and multiphysics simulations to predict temperature and moisture distributions within the bread matrix. This study underscores the essential role of mathematics in enhancing process understanding and modeling accuracy, and highlights future research opportunities that integrate computational approaches into food engineering.